2007
DOI: 10.1021/ie070415u
|View full text |Cite
|
Sign up to set email alerts
|

Do All Carbonized Charcoals Have the Same Chemical Structure? 2. A Model of the Chemical Structure of Carbonized Charcoal

Abstract: Charcoals and carbonized charcoals (i.e., biocarbons) were prepared from a wide variety of biomass substrates, including pure sugars containing five- and six-membered rings with furanose and pyranose configurations, lignin, agricultural residues (corncob and nut shells), and a hard wood. These biocarbons were subject to proximate and elemental analysis, gas sorption analysis, and analysis by inductively coupled plasma mass spectroscopy (ICP-MS), scanning electron microscopy (SEM), X-ray diffraction (XRD), elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(185 citation statements)
references
References 43 publications
11
166
2
6
Order By: Relevance
“…Bourke et al (23) found that the lack of atomic pore space within the crystallite carbon layers as well as recondensation and trapping of VM in pores reduces the SA.…”
Section: Composite Char -Turbostratic Crystallites Embedded In a Low-mentioning
confidence: 99%
“…Bourke et al (23) found that the lack of atomic pore space within the crystallite carbon layers as well as recondensation and trapping of VM in pores reduces the SA.…”
Section: Composite Char -Turbostratic Crystallites Embedded In a Low-mentioning
confidence: 99%
“…In the process of pyrolysis, the biochar surface forms many free radicals [16] that are generated by oxygen atoms and inorganic impurities of the feedstock [36]. The free radical content varies with pyrolytic temperature.…”
Section: The Degradation Products Of Cp In Soil and Biocharmentioning
confidence: 99%
“…Thermogravimetric studies show that during the carbonization of a lignocellulosic material, carboxyl groups are the most thermolabile oxygen groups, as they can be decomposed as CD 2 at temperatures in the range of 100 to 400 °C, while carboxylic anhydrides and lactones decompose in the range of 430 660 °C. The other types of oxygen groups (phenols, ethers, carbonyls and quinones) are decomposed thermally as either CD or CD 2 at temperatures above 600 °C, the pyrone structures being the most thermally stable (decomposing at 900 to 1,200 °C) (Bourke et al, 2007). Thus, to control the acidic or basic nature of the activated carbon produced, except for the intrinsic properties of the precursor material, the temperature and heating rates must be carefully controlled in the carbonization and activation process (Dliveira & França, 2008).…”
Section: Adsorbent Characterizationmentioning
confidence: 99%